Pattern and cost of growth and nutrient deposition in fish and shrimp: Potential implications and applications - P. Bureau, Dominique; A. Azevedo, Paula; Tapia-Salazar, Mireya; Cuzon, Gérard (Avances en Nutrición Acuicola, 2019)
Growth is a factor of prime importance in aquaculture. A better understanding of growth could result in significant benefits in terms of productivity, sustainability and profitability for aquaculture operations, provided this greater understanding is translated into relevant and simple applications. The use of growth models, for example, offers an objective and practical way of describing pattern of growth and predicting production. Growth involves the accretion of body components. The amounts of body components deposited and the cost of depositing these components are the main factors determining feed requirement and waste outputs of fish, shrimp and other aquatic animals. This paper examines growth and nutrients deposition and utilization of fish and, to some extent, shrimp under aquaculture conditions. Simple approaches or models for describing and predicting growth, body composition, and feed requirement of fish and shrimp under aquaculture conditions are presented.